(untitled) (L’uomo nero. Materiali per una storia delle arti della modernità, 2022)
A man lying down in a lawn, lied on an elbow, enjoyed his own freedom; he felt happy even if a big factory throwing up smoke threatens on the background. However, the idleness does not last long. Two policemen stopped the reverie of the vagabond, toke him and forced to work; “work make men free”, before Auschwitz. Forcing to the freedom – a different freedom than that one can be thought by stargazing in suburbs – included the obligation to the work. The essay analyzed the topic of the right to the idleness in painting and film works by Georges Seurat, Paul Signac, René Clair, and Marija Lebedeva.